Hypoxia-induced mixed-lineage leukemia 1 regulates glioma stem cell tumorigenic potential - Heddleston, J M (Nature Publishing Group, 2012)
Normal stem cells reside in functional niches critical for self-renewal and maintenance. Neural and hematopoietic stem cell niches, in particular, are characterized by restricted availability of oxygen and the resulting regulation by hypoxia-inducible factors (HIFs). Glioblastoma multiforme (GBM) is the most common malignant brain tumor and also contains high degrees of hypoxia. Heterogeneity within the neoplastic compartment has been well characterized in GBM and may be derived from genetic and epigenetic sources that co-evolve during malignant progression. Recent experimental evidence has supported the importance of hypoxia in glioma stem cell (GSC) niches. We hypothesized that HIFs require epigenetic-modifying proteins to promote tumor malignancy in GBM. Here we demonstrate that in GBM the histone methyltransferase mixed-lineage leukemia 1 (MLL1) is induced by hypoxia and enhances hypoxic responses. Loss of MLL1 reduces the expression of HIF transcripts and HIF2α protein. Targeting MLL1 by RNA interference inhibited the expression of HIF2α and target genes, including vascular endothelial growth factor (VEGF). GSCs expressed higher levels of MLL1 than matched non-stem tumor cells and depletion of MLL1 reduced GSC self-renewal, growth, and tumorigenicity. These studies have uncovered a novel mechanism mediating tumor hypoxic responses linking microenvironmental regulation of epigenetic-modifying proteins to cellular heterogeneity and provide rationale for the design of more sophisticated clinical approaches targeting epigenetic regulation.